Contemporary perspectives on research on bullying and victimization in early childhood education - Saracho, Olivia N. (Contemporary perspectives on research in early childhood education., 2016)
While the research on bullying and peer victimization has increased considerably over the past 20 years, a number of studies are emerging that document mixed results of bullying and prevention programs. During the last decades, several special issues devoted to research on bullying and victimization have been published in national and international scholarly journals. Based on the increase of published articles on bullying and victimization in journals, textbooks, government reports, and documents in professional organizations, it is timely for a special volume on research on bullying and victimization to appear in the series on Contemporary Perspectives in Early Childhood Education. The purpose of this volume is to share a collection of research strands on bullying and victimization of young children. It describes the historical roots and suggests anti-bullying programs and strategies to decrease bullying and victimization. The bullying and victimization volume can be a valuable tool to researchers who are conducting studies in that area. It focuses on important historical and contemporary issues on bullying and victimization in early childhood education (ages 0 to 8) to provide the information necessary to make judgments about these issues. It also motivates and guides researchers to explore gaps on research on bullying and victimization.